Tilted magnetisation for domain wall pinning in racetrack memory - Jin, Tianli (2020)
The interest in spintronics devices based on domain wall (DW) motion has gained attention for many years. However, the stochastic behaviour of DW motion is still a fundamental issue for the practical implementation of DW devices. In this study, we demonstrate that effective domain wall pinning can be achieved by using exchange interaction between Co/Ni multilayer with perpendicular magnetic anisotropy (PMA) and Co layer with in-plane magnetic anisotropy (IMA) to create locally tilted magnetisation. The strength of exchange interaction is tuned by varying the thickness of spacer layer Pt between the PMA and IMA layers, thus forming different tilt angles. Micromagnetic simulations were performed to verify the relation between pinning field and magnetisation tilt angle. Polar Kerr microscopy shows the current-driven DW pinning and depinning in the Co/Ni multilayer device with Co crossbars, where the thickness of spacer layer Pt is 1 nm. The proposed approach can potentially be used in future DW memory device applications.